Doxazosin Stimulates Galectin-3 Expression and Collagen Synthesis in HL-1 Cardiomyocytes Independent of Protein Kinase C Pathway - Qian, Xiaoqian; Li, Mingyang; Wagner, Mary B.; Chen, Guangping; Song, Xiang (Frontiers in Pharmacology, 2016)
Doxazosin, a drug commonly prescribed for hypertension and prostate disease, increases heart failure risk. However, the underlying mechanism remains unclear. Galectin-3 is an important mediator that plays a pathogenic role in cardiac hypertrophy and heart failure. In the present study, we investigated whether doxazosin could stimulate galectin-3 expression and collagen synthesis in cultured HL-1 cardiomyocytes. We found that doxazosin dose-dependently induced galectin-3 protein expression, with a statistically significant increase in expression with a dose as low as 0.01 μM. Doxazosin upregulated collagen I and α-smooth muscle actin (α-SMA) protein levels and also induced apoptotic protein caspase-3 in HL-1 cardiomyocytes. Although we previously reported that activation of protein kinase C (PKC) stimulates galectin-3 expression, blocking the PKC pathway with the PKC inhibitor chelerythrine did not prevent doxazosin-induced galectin-3 and collagen expression. Consistently, doxazosin treatment did not alter total and phosphorylated PKC. These results suggest that doxazosin-stimulated galectin-3 is independent of PKC pathway. To determine if the α1-adrenergic pathway is involved, we pretreated the cells with the irreversible α-adrenergic receptor blocker phenoxybenzamine and found that doxazosin-stimulated galectin-3 and collagen expression was similar to controls, suggesting that doxazosin acts independently of α1-adrenergic receptor blockade. Collectively, we show a novel effect of doxazosin on cardiomycytes by stimulating heart fibrosis factor galectin-3 expression. The mechanism of action of doxazosin is not mediated through either activation of the PKC pathway or antagonism of α1-adrenergic receptors.